Mapping the proteo-genomic convergence of human diseases - Pietzner, Maik; Wheeler, Eleanor; Carrasco-Zanini, Julia; Cortes, Adrian; Koprulu, Mine; Wörheide, Maria A; Oerton, Erin; Cook, James; Stewart, Isobel D; Kerrison, Nicola D; Luan, Jian'an; Raffler, Johannes; et al. (Science (American Association for the Advancement of Science), 2021)
Characterization of the genetic regulation of proteins is essential for understanding disease etiology and developing therapies. We identified 10,674 genetic associations for 3892 plasma proteins to create a cis-anchored gene-protein-disease map of 1859 connections that highlights strong cross-disease biological convergence. This proteo-genomic map provides a framework to connect etiologically related diseases, to provide biological context for new or emerging disorders, and to integrate different biological domains to establish mechanisms for known gene-disease links. Our results identify proteo-genomic connections within and between diseases and establish the value of cis-protein variants for annotation of likely causal disease genes at loci identified in genome-wide association studies, thereby addressing a major barrier to experimental validation and clinical translation of genetic discoveries.